If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2y(-2x + 4) = 8 Reorder the terms: 4x + 2y(4 + -2x) = 8 4x + (4 * 2y + -2x * 2y) = 8 Reorder the terms: 4x + (-4xy + 8y) = 8 4x + (-4xy + 8y) = 8 Solving 4x + -4xy + 8y = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8y' to each side of the equation. 4x + -4xy + 8y + -8y = 8 + -8y Combine like terms: 8y + -8y = 0 4x + -4xy + 0 = 8 + -8y 4x + -4xy = 8 + -8y Reorder the terms: -8 + 4x + -4xy + 8y = 8 + -8y + -8 + 8y Reorder the terms: -8 + 4x + -4xy + 8y = 8 + -8 + -8y + 8y Combine like terms: 8 + -8 = 0 -8 + 4x + -4xy + 8y = 0 + -8y + 8y -8 + 4x + -4xy + 8y = -8y + 8y Combine like terms: -8y + 8y = 0 -8 + 4x + -4xy + 8y = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-2 + x + -1xy + 2y) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-2 + x + -1xy + 2y)' equal to zero and attempt to solve: Simplifying -2 + x + -1xy + 2y = 0 Solving -2 + x + -1xy + 2y = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + x + -1xy + 2 + 2y = 0 + 2 Reorder the terms: -2 + 2 + x + -1xy + 2y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x + -1xy + 2y = 0 + 2 x + -1xy + 2y = 0 + 2 Combine like terms: 0 + 2 = 2 x + -1xy + 2y = 2 Add '-2y' to each side of the equation. x + -1xy + 2y + -2y = 2 + -2y Combine like terms: 2y + -2y = 0 x + -1xy + 0 = 2 + -2y x + -1xy = 2 + -2y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| f(x)=25(60-25) | | 147x^2+14x-70=91x^2-450x | | 240+x= | | z^2=9/2z | | 225x^2-1= | | f(x)=10(60-10) | | 4a+2-3a-4= | | f+s=19 | | -3(2n+2)=15 | | f(x)=10(60-x) | | X(x-2)(x-2)=0 | | 19=f+s | | 5r^-3w^5/3r^3w^-2 | | 2r^2+6r=3 | | -1/2y-(8-5)=3y-2 | | 2(2x-4)=3x-18+3x | | 6z+3= | | 3x^2-8x+5=1 | | ln(6-4x)=ln(5-5x) | | x=2x-54 | | 7(x+2)=231 | | 78(-6x+14)= | | 7x^2-32x-12=0 | | 21x^3+15x^2-6x=0 | | -42=6x+30 | | -7(2t+9)=-119 | | 4x+3(2x-13)=11 | | 4(f-2)=8 | | 32q^2-8q=0 | | 36=19q+18-10q | | 14x=-36 | | 10(s-5)=-122 |